RNAcentral: a comprehensive database of non-coding RNA sequences - Petrov, Anton I; Kay, Simon J E; Kalvari, Ioanna; Howe, Kevin L; Gray, Kristian A; Bruford, Elspeth A; Kersey, Paul J; Cochrane, Guy; Finn, Robert D; Bateman, Alex; Kozomara, Ana; Griffiths-Jones, Sam; et al. (Nucleic acids research, 2017)
RNAcentral is a database of non-coding RNA (ncRNA) sequences that aggregates data from specialised ncRNA resources and provides a single entry point for accessing ncRNA sequences of all ncRNA types from all organisms. Since its launch in 2014, RNAcentral has integrated twelve new resources, taking the total number of collaborating database to 22, and began importing new types of data, such as modified nucleotides from MODOMICS and PDB. We created new species-specific identifiers that refer to unique RNA sequences within a context of single species. The website has been subject to continuous improvements focusing on text and sequence similarity searches as well as genome browsing functionality. All RNAcentral data is provided for free and is available for browsing, bulk downloads, and programmatic access at http://rnacentral.org/.